Bacterial diversity in some selected agricultural food products - Ali, Amna; Haider, Muhammad Saleem; Hanif, Sana; Ashfaq, Muhammad (Bangladesh Journal of Botany, 2015)
A total of 27 bacterial strains were isolated from apple, potato, turnip, onion, cucumber, zinger, lemon, spinach, radish and mint marketted in Labore, Pakistan. Highest frequency of occurrence (4%) was recorded for each of Enterobacter aggglomerans, Ensifer adhaerens and Bordetella pertussis, Brassica rapa and Kurthia gibsonii showed 30% frequency of occurrence. Frequency of all other bacterial strain ranged from 10 - 20%. Highest number (7) of bacterial speices were recorded from lemon and potato while the minimum number (4) was represented by each of apple, onion, ginger, spinach and radish. DOI: http://dx.doi.org/10.3329/bjb.v43i2.21676 Bangladesh J. Bot. 43(2): 219-222, 2014 (September)